Impact of Coffee Tourist Attractions on Visit Intentions of Generation Y and Z - Mukti, Bentar Sagara; Priyambodo, Tri Kuntoro; Irwan, Siti Nurul Rofiqo (Lasigo Akademia Indonesia, 2024)
This study investigates the influence of coffee tourist attractions (CTA) on the visit intentions of Generation Y and Generation Z. Utilizing a quantitative research framework, surveys were conducted to assess how product quality, service quality, and atmospheric of coffee shops as tourist destinations. The sample consisted of 314 respondents from Yogyakarta, including both generations. The results demonstrate that both Generation Y and Z are significantly influenced by the quality of products, services, and coffee shop atmosphere with Generation Y placing greater emphasis on personal recommendations and traditional marketing, while Generation Z relies more on digital interactions and social media. These findings highlight the importance of tailored marketing strategies to effectively attract each generational cohort. The study concludes that enhancing product quality, service, and atmosphere of coffee shops can positively impact their attractiveness as tourist destinations for both Generation Y and Z.